Tovuz Clashes: A Message from Russia to Azerbaijan: Understanding the Message Behind the Tovuz Clashes (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The Armenian-Turkish conflicts, which have a much older history, resurfaced in the South Caucasus from the late 1980s with the weakening of the Soviet Central authority. As the conflicts turned into a hot war, including Nagorno-Karabakh, 20 of Azerbaijani territories were occupied by Armenia. Although the war seems to have ended with the 1994 Bishkek Protocol, no final agreement was reached and relative peace was violated by frequent conflicts. The most recent July clashes between the Armenia and Azerbaijan, unlike previous ones, took place not around Nagorno-Karabakh, but on the international border of the two countries. The emergence of the conflicts in Tovuz, where the land and railways which connect Azerbaijan to the West and the important oil and natural gas pipelines carrying the Caspian Basin natural resources to the West, has brought many question marks with it. The risk of paralyzing the Azerbaijani economy and having great consequences shows that the Tovuz conflicts are not just an action taken on the initiative of Armenia. In this context, Russia, which tries to keep its ‘circle of influence’ under control with the instabilities it created in the Post-Soviet geography, comes to the fore. In the recent times, the increasing importance of Azerbaijan in the energy security of the West, the dismissal of Russian-backed politicians in the Azerbaijani administration and the deactivation of the Russian pipelines while bringing its own energy resources to the world market increase the possibility of the Russian hand behind these events. In addition, alternative scenarios such as regional competition of Russia and Turkey related to the background of the conflicts, economic and health problems caused by the pandemic process. However, the attitude of Russia during and after the conflict reinforces the possibility that the Tovuz incidents were a message by the Russians. This paper will shed light on the possible causes of the conflict and will further elucidate how this conflict was actually a message by Russia towards Azerbaijan.